Public Communication in the Campaign to Utilize Biogas from Animal Manure as Renewable Energy - Kornelia Johana; Suswinda Ningsih; Vania Utamie Subiakto; Cece Sutisna (Dinasti Publisher, 2024)
This research analyzes the public communication strategies used in the campaign to utilize biogas from livestock manure as renewable energy. This research understands the effectiveness of public communication strategies in raising public awareness about the potential of renewable energy from animal waste. The research method used is a qualitative approach, campaign theories, such as innovation diffusion theory and participatory communication theory, to analyze the effectiveness of the communication strategies used. Data were collected through interviews with campaign-related stakeholders, direct observation, and analysis of related documents. The results showed that public communication strategies were used, such as counseling, workshops, social media campaigns and mass media, successfully increasing the understanding of public interest in the utilization of livestock manure biogas. The campaign “Green Energy Revolution: Biogas for a Sustainable Future.” The campaign will focus on promoting the utilization of biogas from livestock manure as an environmentally friendly and sustainable renewable energy solution. The findings provide insights into the development of effective public communication strategies in supporting the utilization of biogas, livestock manure as a renewable energy source at the local level. This research contributes to positive, sustainable policy and program development promoting animal manure renewable energy. A better understanding of effective public communication strategies, it is expected that the community will be more involved and supportive of efforts to create a sustainable and environmentally friendly energy future